Impact of Agrotechnology Innovation, Human Resource Quality, And Capital Investment In Improving Profitability With Plantation Productivity As A Mediator at PT. TSB Plantation Company - wasik, zainul (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the influence of agro-technology innovation, human resource (HR) quality, and capital investment on profitability, with plantation productivity as a mediating variable at PT. TSB, a plantation company facing intense industry competition. Methodology: A quantitative approach with path analysis was employed. Data were collected through questionnaires, observations, and company documentation, then analyzed using Structural Equation Modeling (SEM) via SmartPLS software. The sample included employees and relevant management personnel at PT. TSB. Results: Agro-technology innovation, HR quality, and capital investment had a positive and significant effect on plantation productivity. Furthermore, plantation productivity positively influenced profitability. Productivity also acted as a partial mediator in the relationship between agro-technology innovation, HR quality, capital investment, and profitability. Findings: Enhancing agro-technology innovation, HR quality, and capital investment can boost plantation productivity, ultimately increasing PT. TSB’s profitability. The study highlights the importance of optimizing technology, HR training, and capital allocation for operational efficiency and competitive advantage. Novelty: This study fills a research gap by comprehensively testing a mediation model of plantation productivity, which has not been widely explored in the context of Indonesian plantation companies.. Conclusion: To improve profitability, PT. TSB should prioritize agro-technology adoption, HR development, and strategic capital investments, leveraging productivity as a key mediating factor. Type of Paper: Empirical research.